SIKAP MASYARAKAT KUDUS TERHADAP UNDANG-UNDANG TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Anisa Listiana dan M. Widjanarko (MUWAZAH : jurnal kajian gender, 2013)
This study is about PKDRT law. It gives us information that domestic violence is a real thing that happens in our society, especially in Kudus. On the one hand, civil society actually has a formula to prevent the authority and rights of their family life with PKDRT (legal elimination of domestic violence) law. On the other hand, the government has a responsibility to eliminate violence, force and coercion in family life as referred to in 11, 12 and 13 of Law No. 23 of 2004. But the most important thing is that the courage of society to show concern and the seriousness of the government to take action when violence occurs. This research shows that domestic violence is a result of power imbalance between the weak dan the strong in our society where many women that represent the weak became a victim.